Kontestasi Otoritas Keagamaan di Era Disrupsi AI: Analisis Netnografi terhadap Resepsi Dakwah Islam di TikTok - Rina Rohmatun Hidayah (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2026)
The emergence of generative artificial intelligence (Generative AI) in cyber-da'wah institutions has brought a serious theological shock to the establishment of traditional religious authority in Indonesia. This cutting-edge technological development has given birth to a new pluralism of religious authority on TikTok, manifesting in three main forms: computational (AI), conventional-hybrid, and curative (content aggregator). This study aims to critically analyze the contestation of virtual religious authority through three account objects: @islam.dan.kehidup, @kajianbrebes.id, and @syam_elmarusy. Employing Robert Kozinets' netnographic method, data were collected through cyber-observation of content, narrative texts, and comment section interactions. The analytical frameworks used are Jean Baudrillard's Simulacra theory to dissect the visual hyperreality space, and Stuart Hall's Encoding/Decoding theory to map the reception positions of Muslim netizens. The results indicate that curative accounts successfully trigger instant emotional catharsis through the manipulation of a melancholy visual aesthetic. Conversely, AI-based da'i (preachers) provoke massive theological resistance (oppositional position) because they are perceived to reduce the sacredness of sanad (scholarly lineage) and eliminate the spiritual ruh (soul) dimension of human humanity. Meanwhile, the conventional-hybrid model maintains the highest legitimate control by integrating organic human charisma with cyber-agility adaptation.This study provides an academic contribution to understanding the dynamics of da'wah in the algorithmic era, while emphasizing that no matter how sophisticated digital disruption offers an boundless simulation of visual piety, sacred boundaries regarding morality, authenticity, and human scholarly lineage remain the absolute determinants of religious authority for the cyber-Muslim community.